A review on the role of co-processed excipients in tablet formulations - Ankita S. Burande; Shrushti P. Dhakare; Ayusha O. Dondulkar; Tilottama M. Gatkine; Deepti O. Bhagchandani; Minal S. Sonule; Vinod M. Thakare; Satyendra K. Prasad (Hybrid Advances)
Multifunctional excipients are becoming more popular since they eliminate the need to combine numerous excipients in a mixture, simplifying the drug formulation process. The multifunctional excipients include co-processed excipients, which add additional functions to the formulation. Since, individual excipients might not constantly produce the desired results during the manufacturing and development of a specific API, researchers are focusing on developing multifunctional excipients with improved quality and satisfy the cost-requirements of formulation scientist. This review includes limitations of existing excipients, benefits of co-processed excipients, their production process, and information on different co-processed excipients from literature, their drawbacks, regulatory consideration, evaluation techniques and potential future developments. As more novel combinations of excipients and novel techniques for co-processing are existing, co-processed excipients will surely draw interest from the academics and pharmaceutical companies. In addition, it permits the development and application of solo multifunctional excipients as an alternative of using numerous excipients in formulation.